What makes supported internships an effective approach to VET? - Jill Hanson; Debs Robinson; Geraldene Codina (Nordic Journal of Comparative and International Education, 2022)
Internationally, there have been varied attempts to secure the inclusion of young people with Special Educational Needs and Disabilities (SEND) in Vocational Education and Training (VET). This paper investigates supported internships (SIs), which are programmes that include college courses in numeracy and literacy, workplace learning, and broader life skill development. Drawing on an empirical study of one SI in England, this paper focuses on the pedagogic structure of SIs to explore how systematic instruction combines with elements of the workplace environment to bring about successful vocational learning for young people with SEND. It considers whether the expansive-restrictive conceptualisation of apprenticeship learning explains successful outcomes within an SI. A case study approach using a qualitative methodology of semi-structured interviews was adopted to explore the experiences of people involved in the SI. These included two job coaches, four colleagues, six interns and three graduates from the SI. Thematic analysis revealed this SI facilitates workplace learning for young people with SEND because it models an expansive (not reductive) approach to internships. Systematic instruction did not result in restrictive learning because of role design and broader organisational features. A key facilitating aspect was that the design of the internship fostered opportunities to develop identity through crossing boundaries. Implications for the design of SIs (to facilitate social inclusion and ensure employment outcomes for young people with SEND) are discussed.